Serotypes, Antibiotic Susceptibilities, and Multi-Locus Sequence Type Profiles of Streptococcus agalactiae Isolates Circulating in Beijing, China - Wang, Ping; Tong, Jing-jing; Ma, Xiu-hua; Song, Feng-li; Fan, Ling; Guo, Cui-mei; Shi, Wei; Yu, Sang-jie; Yao, Kai-hu; Yang, Yong-hong (PLOS ONE, 2015)
Background To investigate the serotypes, antibiotic susceptibilities, and multi-locus sequence type (MLST) profiles of Streptococcus agalactiae (S. agalactiae) in Beijing to provide references for the prevention and treatment of S. agalactiae infections. Methods All isolates were identified using the CAMP test and the latex-agglutination assay and serotyped using a Strep-B-Latex kit, after which they were assessed for antibiotic susceptibility, macrolide-resistance genes, and MLST profiles. Results In total, 56 S. agalactiae isolates were identified in 863 pregnant women (6.5%). Serotypes Ia, Ib, II, III, and V were identified, among which types III (32.1%), Ia (17.9%), Ib (16.1%), and V (14.3%) were the predominant serotypes. All isolates were susceptible to penicillin and ceftriaxone. The nonsusceptiblity rates measured for erythromycin, clarithromycin, azithromycin, telithromycin, clindamycin, tetracycline, and levofloxacin were 85.7%, 92.9%, 98.2%, 30.4%, 73.2%, 91%, and 39.3%, respectively. We identified 14 sequence types (STs) for the 56 isolates, among which ST19 (30.4%) was predominant. The rate of fluoroquinolone resistance was higher in serotype III than in the other serotypes. Among the 44 erythromycin-resistant isolates, 32 (72.7%) carried ermB. Conclusion S. agalactiae isolates of the serotypes Ia, Ib, III, and V are common in Beijing. Among the S. agalactiae isolates, the macrolide and clindamycin resistance rates are extremely high. Most of the erythromycin-resistant isolates carry ermB.